Evaluation of hazardous waste transportation firms by using a two step fuzzy-AHP and TOPSIS methodology - Gumus, Alev Taskin (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Hazardous wastes are likely to cause danger to human health and/or environment. Safe transportation of them is so important. Consequently, selection of the right and most appropriate transportation firm is an important problem for hazardous waste generators. In this paper, a two step methodology is structured to evaluate hazardous waste transportation firms containing the methods of fuzzy-AHP and TOPSIS. And a numerical example is presented to clarify the methodology. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Hazardous waste; Transportation firm evaluation; Fuzzy-AHP; TOPSIS; GROUP DECISION-MAKING; MANAGEMENT; EXTENSION; SELECTION; SYSTEMS; DELPHI; Computer Science; Engineering; Operations Research & Management Science